PEMBENAHAN PENGELOLAAN KEUANGAN DANA DESA: STUDI KASUS DESA SENGONBUGEL - Jumaiyah Jumaiyah; Wahidullah Wahidullah (Media Riset Akuntansi, Auditing & Informasi, 2019)
The purpose of this study is to find out how the village fund management incurred in 2016, and also what does the new leader do to improve the village performance. The method in this study is phenomenological qualitative by collecting measurement data, in-depth interviews and documentation. The results show that temporary officials, managed fund well to established many programs to increase the community wealth.